2011
DOI: 10.1111/j.2042-3292.2011.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep digital flexor tendonopathy in the foot

Abstract: Summary Tendonopathy of the distal portion of the deep digital flexor tendon is a newly recognised, important cause of foot lameness in horses. Although the pathological morphology of lesions has been well described, the aetiopathogenesis remains uncertain. A conclusive diagnosis can only be made with magnetic resonance imaging, but the results of a thorough clinical examination, including regional analgesia and other imaging modalities may lead to a strong suspicion of deep digital flexor tendonopathy in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 49 publications
2
46
0
Order By: Relevance
“…In this study the length of the lesion was 79,59 mm in one case and 55,30 mm in the second case. Core lesions are characterized as collagen necrosis, fibroplasia and fibrocartilagenous metaplasia (Schramme 2011). Dorsal abrasions are usually seen concurrently with navicular bursa pathologies as was in one case in that study (Fig.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…In this study the length of the lesion was 79,59 mm in one case and 55,30 mm in the second case. Core lesions are characterized as collagen necrosis, fibroplasia and fibrocartilagenous metaplasia (Schramme 2011). Dorsal abrasions are usually seen concurrently with navicular bursa pathologies as was in one case in that study (Fig.…”
Section: Resultsmentioning
confidence: 51%
“…Predisposing factors may be connected with hoof conformation, distal phalanx angle, angle of the DDFT lying caudally to the navicular bone, athletic discipline, neurectomy and navicular bone disorders (Schramme 2011). There are four main types of the DDFT injuries: core lesions, dorsal abrasions, sagittal plane and oblique splits, insertional lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Horses with foot pain were categorised into groups: (1) primary navicular bone pathology only (NB); (2) lesions of the PTA ± DDFT (PTA); (3) primary DDFT injury only (Schramme, 2011); (4) lesions of the PTA and injuries of other structures in the foot (PTA + other); (5) other, defined as lesions involving other structures within the foot or multiple injuries, excluding the PTA; and (6) unknown in which horses had not undergone an MRI and had no definitive radiological or ultrasonographic abnormality to determine the cause of foot pain. The control horses were those without foot-related pain.…”
Section: Methodsmentioning
confidence: 99%
“…The most common conditions include injury of the deep digital flexor tendon (DDFT) (Dyson et al, , 2005Mair and Kinns, 2005;Dyson and Murray, 2007;Schramme, 2011), or the collateral ligaments (CLs) of the distal interphalangeal (DIP) joint Zubrod et al, 2005;Gutierrez-Nibeyro et al, 2009;Dakin et al, 2009a,b), navicular disease (Barber et al, 2006;Sampson et al, 2009;Sherlock et al, 2008;Dyson, 2010, 2011), and complex injuries involving several structures Sampson et al, 2009). Navicular disease is a term used to refer to lameness associated with pain arising from the distal sesamoid (navicular) bone, with or without injury of the collateral sesamoidean ligament (CSL) and distal sesamoidean impar ligament (DSIL) (known collectively as the podotrochlear apparatus [PTA]) and/or the DDFT (Widmer et al, 2000;Dyson et al, 2005Dyson et al, , 2011a.…”
Section: Introductionmentioning
confidence: 99%
“…Progress in the field of diagnostic imaging has shown that the deep digital flexor tendon (DDFT) (M. flexor digitalis profundus) is one of the most commonly injured structures in sport horses undergoing magnetic resonance imaging for foot pain, with a total prevalence ranging from 30% to 83% (Schramme, 2011). The macroscopic appearance of the tendon as well as its histological structure and various pathohistological lesions has been previously described (Blunden et al, 2006).…”
mentioning
confidence: 99%